High-speed videomicroscopy of sheared carbonyl iron suspensions. (1st February 2023) - Martínez-Cano, Óscar; Morillas, Jose R; Cvek, Martin; Ramírez, Javier; de Vicente, Juan
Abstract: The postyield rheological regime is investigated in sheared magnetic field-responsive composites (i.e. carbonyl iron based magnetorheological fluids). When subjected to uniaxial DC fields, high-speed videomicroscopy techniques and dedicated image analysis tools demonstrate that dispersed magnetic microparticles self-assemble to form concentric layered patterns above a particular shear rate ( γ ˙ R, c ). This critical shear rate for layer formation is dictated by a critical Mason number M n c ∼ 1 that is associated to the destruction of the last doublet in the chain-like aggregates. The number of layers, mean width, percentage of occupation and mean period are found to be very weakly dependent on the shear rate in start-up shearing flow tests. Experimental data for the mean period are in good agreement with an energy minimization theory.